Computed Tomography and Patient Risk: Facts, Perceptions and Uncertainties - Din Muhammad Sohu, Naimatullah Bozdar, Zeeshan Jamal, Inayatullah, Akhtar Hussain Phul,, Rabia Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the role of computed tomography for management of Covid-19. Study design: Prospective study Place and duration of study: Department of Radiology, Ghulam Muhammad Mahar Medical College Teaching Hospital Sukkur from 1st November 2020 to 31st December 2021. Methodology: One hundred cases within various ages 5-55 years for analyzing their risk for CT scanning on them by highlighting the facts related to CT scan, patient perceptions and uncertainties regarding it. A 50 radiologist and 50 emergency doctors were also asked questions regarding their knowledge about CT scan risks and their responses were also documented. However previous CT record of patients suffering from carcinoma was also analyzed for understanding the fact related with CT imaging. Results: The mean age of patients undergoing CT scan was 39.5±5.6 years. There were 55% males who underwent CT scans while 45% females. The usual dosage for various radiological procedure shows that highest dose deliverance was given to the patients of CT pulmonary angiogram and coronary angiography. Only 50% of radiologists knew that CT scan is associated with high risk of malignancies. There were only 10% emergency medical doctors who also knew CT imaging relation with malignancy risk. Only 54% patients considered abdomen pelvic scan to be associated with increasing lifetime risk of cancer while 23% of the patients considered chest scan to be associated with escalating the risk of cancer. Conclusion: Computed tomography scan is related with a high risk of radiation exposure. There is a dire need of perception development and risk understanding with medical professionals and general public for minimizing this risk.